Analyzing Within‐County Hydrogeomorphological Characteristics as a Precursor to Phosphorus Index Modifications. Issue 6 (1st November 2017) - Veith, Tamie L.; Goslee, Sarah C.; Beegle, Doug B.; Weld, Jennifer L.; Kleinman, Peter J. A.
Abstract : Phosphorus (P) site assessment is used nationally and internationally to assess the vulnerability of agricultural fields to P loss and identify high‐risk areas controlling watershed P export. Current efforts to update P site assessment tools must ensure that these tools are representative of the range of conditions to which they will be applied. We sought to identify key parameters available in public GIS data that are descriptive of potential source areas in Pennsylvania and that ensure that modifications of the P Index span all feasible parameter combinations. Relevant soil and topographic variables were compiled for Pennsylvania at 30‐m resolution, and areas within 90 m of permanent streams were extracted. Within each county, k ‐means and classification trees were used to identify and create classification rules for topoedaphic groups. Within counties, two to five groups adequately represented near‐stream complexity, with available water capacity, hydraulic conductivity, and organic matter being the most important environmental variables. Discontinuities across soil survey boundaries made it impossible to develop clusterings beyond the county level. For county‐scale research and management efforts, these groupings provide a manageable approach to identifying representative sites for near‐stream agricultural lands. The full set of representative sites across the state enables evaluation of the P Index throughout the full hydrogeomorphic diversity of Pennsylvania. In future work, we can then combine a set of reasonable management practices with each of the main hydrogeomorphological regions resulting from this study and verify the revised P Index against expert knowledge and simulation results. Core Ideas: Hydraulic properties and organic matter are key for grouping near‐stream soils. Discontinuities across soil surveys prevent modeling regions across counties. Two to five groups per county are sufficient to classify most near‐stream soils. Cluster analysis of environmental data provides a focus for revising the P Index.